Encuentros y desencuentros América entre dos fuegos, 1521-1821 - Moreno Amador, Carlos; Luis Caño Ortigosa, José (Biblioteca Historia de América, 2022)
The meeting between America and Europe began a first historical period that would extend over three centuries, always marked by the differences between two different ways of understanding the relations of domination between the two. This tension, constantly present and expressed in multiple ways, transports us inexorably to a convulsive beginning of the 19th century. A historical moment marked by the rupture, in capital letters, associated with the fall of the Old Regime, of obsolete models of political, economic and social organization, of archaic ways of thinking and acting. In this context, the disagreement in America had been made clear for quite some time. The emancipation processes came to signify, therefore, the confirmation that the American system was in absolute decline. We believe that the set of contributions that make up this work -precisely because of its heterogeneity, because of its different approaches and because it never abandons the overall perspective- contributes as one more grain of sand to the debate and discussion about our common history, about the difficult times that were lived and that never left us.